Racionalidade neoliberal e processos de subgetivação: limites ao poder constituinte, democracia e constituição - Barbiero, Victória Faria (2021)
This Dissertation is part of the Constitutional Jurisdiction Research Line and Democracy and aims to analyze how constitutionalism and democracy today, in order to propose new ways of thinking about these concepts that break with neoliberal rationality and the logic of capital. Through a eminently bibliographical research, the main problem of the analysis is to explore the crisis of Democratic Constitutional States in its genesis. In a first moment it was verified that neoliberal rationality is a new way of seeing the world, which imposes an atomized conception of the subject, associated with a vision individualistic ethics that operate only from economic calculations and metrics. Democracy, in turn, has lost its axiological substance, causing by the depoliticization of the subject. Afterwards, in the second chapter, it appears that the constitution would have its prescriptions conditioned on external factors (of power). There is no real confluence between (political) subordination to the order (legal) constitutionally provided. Finally, the concepts are operationalized of a constituent power that has no limit in time and of the multitude, with the purpose of thinking about new possible horizons for constitutionalism. AND only from a rationality of the common, antagonistic to the rationality neoliberal, that it will be possible to establish dynamics that include rather than exclude. It is concluded that, to achieve a democracy and a radicalized constitution, it is necessary to start from a constituent power, which involves constant mutation and renewal of the multitude.